Clues to immune tolerance: The monogenic autoimmune syndromes - Waterfield, Michael (2010)
Autoimmune disease affects a significant proportion of the population. The etiology of most autoimmune diseases is largely unknown, but it is thought to be multifactorial with both environmental and genetic influences. Rare monogenic autoimmune diseases, however, offer an invaluable window into potential disease mechanisms. In this review, we will discuss the autoimmune polyglandular syndrome (APS1), the immunedysregulation, polyendocrinopathy, enteropathy, X-linked syndrome (IPEX), and autoimmune lymphoproliferative syndrome (ALPS). Significantly, the information gained from the study of these diseases has provided new insights into more common autoimmune disease and have yielded new diagnostics and therapeutic opportunities.